Improving the adherence to COVID-19 preventive measures in the community: Evidence brief for policy - Fulone, Izabela; Barreto, Jorge Otavio Maia; Barberato-Filho, Silvio; Bergamaschi, Cristiane de Cássia; Lopes, Luciane Cruz (Frontiers in Public Health, 2022)
Objectives To identify evidence-based strategies to improve adherence to the preventive measures against the coronavirus disease (COVID-19) at the community level. Method This is an evidence brief for policy, combining research evidence specific to contextual knowledge from stakeholders. A systematic search was performed in 18 electronic databases, gray literature, and a handle search, including only secondary and tertiary studies that focused on the adherence of the general population to COVID-19 preventive measures in the community. Two reviewers, independently, performed the study selection, data extraction, and assessment of the quality of the studies. Relevant evidence has been synthesized to draft evidence-based strategies to improve adherence. These strategies were circulated for external endorsement by stakeholders and final refinement. Endorsement rates >80%, 60–80% and <60% were considered high, moderate, and low respectively. Results Eleven studies, with varying methodological qualities were included: high (n = 3), moderate (n = 3), low (n = 1), and critically low (n = 4). Three evidence based strategies were identified: i. Risk communication; ii. Health education to the general public, and iii. Financial support and access to essential supplies and services. The rates of endorsement were: 83% for risk communication, 83% for health education, and 92% for financial support and access to essential supplies and services. The evidence showed that an increase in knowledge, transparent communication, and public awareness about the risks of COVID-19 and the benefits of adopting preventive measures results in changes in people's attitudes and behavior, which can increase adherence. In addition, the guarantee of support and assistance provides conditions for people to adopt and sustain such measures. Conclusions These strategies can guide future actions and the formulation of public policies to improve adherence to preventive measures in the community during the current COVID-19 pandemic and other epidemics.